A CBCT study of root canal morphology of bilateral maxillary premolars in South Indian population - Priyanka Sivasubramanian, Dr. Kalaivani (Cuestiones de Fisioterapia, 2023)
Background:The objective of this study was to use CBCT to look into the root canal morphology of bilateral maxillary premolars in a South Indian population and associate the results to existing canal morphology classifications.